Letramento literário na escola: desafios e possibilidades a partir da análise do discurso - Souza, Andreza Shirlene Batista de (2015)
Our study aimed contribute to the literary literacy process of high school, so we propose a methodological procedure that track in ways that can collabore for the student to become a more autonym and critical reader, always trying to understand the function and literacy discouse of the paper, through the fundamental contributions of AD, as also motivate him to have aesthetic experience. The choice of the theme was given by observing that the students showed disinterest in reading and difficulties to understand the meaning of literary genres, likewise the literature develop an essential role for the subjects integral formation. Authors such as Maingueneau (1996), (1997) and (2012); Orlandi (2009); Cosson (2014a) and (2014b); Candido (1995) and (1999); Compagnon (2009), Jouve (2012) and Renato Melo (2005) among others, formed the theoretical basis for the development of this research, corroborating for the validation of the theme. The methodology used was action research, with lessons analysis; diary researcher; intervention; activities; questionnaire, interviews and production of text with 30 students of the third year of high school in a semi-comprehensive school in the metropolitan region of Recife. Based on interaction situations it was found that the practice of literary reading as well as its development is precious little accosted in class, reflecting in the lack of motivation of students to read as well as its analysis in parallel. From the experiences of interventions, we concluded that there was an awakening to the reading of literary genres, linking aesthetic pleasure to the need to generate knowledge (making it clear that is not given in a closed form, but unsettling), thus improving the literary formation of students as ti the vast majority changed the view analytical and conclusive for these texts.